INNOVATIVE SOLUTIONS FOR THE PRODUCTION OF BRICKS FROM WASTEWATER TREATMENT SLUDGE - POPESCU, Gabriel; JIANU, Nicoleta-Raluca; MOGA, Ioana-Corina; ANDREI, Mădălina-Teodora; CHIVOIU, Aneta; CIORNEI, Laurențiu; SIMION, Mirela (Annals of Spiru Haret University. Economic Series, 2022)
Based on the need to recover various wastes such as waste from wastewater treatment plants, it is proposed to use sludge in the manufacture of various building materials as bricks. So far, bricks made of different materials and combinations of classical materials as burnt clay, cement, sand, but also of other unconventional materials, most of them coming from different wastes, are used in construction. In order to use the sludge for bricks fabrication, it is necessary to inert it and to obtain a moisture content below 80%. Also, the physico-chemical and ecological parameters must be suitable for sludge utilization and their values must be situated within the limits imposed by legislation. So, the sludge is centrifuged in order to reduce the moisture content from (90-95)% to a maximum of 80%, treated, then the sludge batches are characterised and finally the sludge is recovered by inert cement.